2019
DOI: 10.5194/isprs-archives-xlii-2-w12-155-2019
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Events in Video Sequence of Video-Eeg Monitoring

Abstract: <p><strong>Abstract.</strong> In this paper, an algorithm for automated detecting diagnostic events in video channel of video and electroencephalographic (EEG) monitoring data is presented. The analysis of video sequences is focused on identifying a group of frames with high or very low (depending on the type of seizure) dynamics of informative areas according to a criterion calculated during processing of the optical flow. The preliminary results of the analysis of real clinical data are giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Analysis of publications in the domain of detecting seizures from video sequences showed that the most common approach is based on the analysis of optical flow. In works (Murashov, 2019;Murashov, 2019a) it was proposed to detect diagnostic events using the measure, characterizing the degree of mobility of the region of interest. The region of interest is the part of the frame where the patient is located.…”
Section: Computation Of Optical Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of publications in the domain of detecting seizures from video sequences showed that the most common approach is based on the analysis of optical flow. In works (Murashov, 2019;Murashov, 2019a) it was proposed to detect diagnostic events using the measure, characterizing the degree of mobility of the region of interest. The region of interest is the part of the frame where the patient is located.…”
Section: Computation Of Optical Flowmentioning
confidence: 99%
“…Previously, the authors of (Murashov, 2019;Murashov, 2019a) proposed to detect events in a video recording by the magnitude of the optical flow, which characterizes the degree of mobility of the frame area in which the patient is located. The algorithm was designed to detect both convulsive and non-convulsive seizures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, several methods have been proposed for the automatic detection of seizures from EEG data [1 -5]. In [6,7], the authors proposed an algorithm for automatic detection of seizures based on the analysis of quantitative characteristics of facial expressions in video sequences. In a video sequence using the magnitude of the optical flow, a group of frames with high scene dynamics is detected.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose an algorithm for synchronous analysis of video sequences and EEG signals, based on a combination of previously developed methods described in [4,6,7], which allows differentiating an epileptic seizure from artifacts caused by chewing and moving. The proposed algorithm is capable of detecting two types of diagnostic events in video EEG data taken from patients with brain injury.…”
Section: Introductionmentioning
confidence: 99%